The OECD potential output estimation methodology - Chalaux, Thomas,Guillemette, Yvan (OECD, 2019)
This paper describes the methodology used in the OECD Economics Department to produce historical estimates and short-run projections of potential output. These estimates are used mainly in the OECD Economic Outlook, in country surveys and as starting point for long-run scenarios. Total-economy potential output is modelled using a constant-returns-to-scale Cobb-Douglas production function with fixed factor shares. The three main inputs are labour, fixed capital excluding housing and labour efficiency, the latter obtained as a decomposition residual. The trend unemployment rate is estimated by Kalman filtering within a forward-looking Phillips curve. Other trend components are obtained by HP-filtering but labour efficiency and the labour force participation rate are cyclically adjusted before filtering to help alleviate the end-point problem associated with filters. This pre-filtering cyclical adjustment is especially helpful at cyclical turning points. It helps to lower the cyclicality of potential output as well as the extent of future revisions.
10.1787/4357c723-en
Keywords: Amtsdruckschrift; Graue Literatur; Economics; Potential output; potential growth; labour efficiency; output gap; NAIRU; capital stock